KORELASI POLA ASUH ORANG TUA DENGAN DISIPLIN BELAJAR SISWA KELAS VI SD GUGUS VIII SUKAWATI TAHUN AJARAN 2017/2018 - Puspitasari, Ni Luh Putu Diah (Journal for Lesson and Learning Studies, 2018)
This study aims to: (1) To know the quality of parenting pattern of the sixth grade students of SD Gugus VIII Sukawati 2017/2018 (2) To know the quality of the discipline of the students of grade VI SD Gugus VIII Sukawati 2017/2018 (3) To know whether there is correlation parenting with the discipline of learning grade 6 students SD Gugus VIII Sukawati 2017/2018. This research is an ex-post facto research. The population of this research is the students of class VI in SD Gugus VIII Sukawati which amounted to 168 students. The sample of research was taken by proportional random sampling technique which amounted to 113 students. Data on parenting and student learning discipline was taken by questionnaire technique. The data obtained were analyzed by qualitative descriptive technique, while to test the research hypothesis used the moment product correlation. Based on the results can be showed that (1) The quality of parenting of the students of SD Gugus VIII Sukawati in the 2017/2018 academic year was quite good, because the average parenting scores were 62.82 and within the range of 59.25 ≤  <65,75 . (2) The quality of student discipline of SD Gugus VIII Sukawati in the 2017/2018 academic year is quite good, because the average learning discipline is 68.28 and is in the range of 63.96 ≤  <70.54. And (3) There is correlation between parenting pattern of student with discipline of studying grade 6 student of SD Negeri Gugus VIII Sukawati academic year 2017/2018. This is evidenced by the correlation coefficient of parenting parents with the discipline of learning results obtained research (rxy) of 0.987 while rxv table (005; N-2) obtained for 0.195. Since the price (rxy) results are in the range of 0.800 to 1.00 then the correlation is high.